Smart Rural Development: Using Information Technology for Sustainable Rural Planning - Fayaz Gul Mazloum Yar; Mohammad Edris Naderi (Jurnal Syntax Transformation, 2025)
Sustainable rural development is critical to improving the economic, social and environmental well-being of rural communities. However, challenges such as inadequate infrastructure and limited access to essential services impede progress. Information and Communication Technology (ICT) offers innovative solutions to overcome these barriers. This research aims to explore the role of ICT in sustainable rural development, focusing on its applications in the agriculture, health, education and governance sectors. The research used a mixed approach, combining policy analysis, stakeholder interviews, case studies, as well as secondary data analysis and spatial modeling. Data were collected through surveys and GIS data analysis to identify the role of ICTs in sustainable rural development. Findings show that the use of ICTs, such as GIS and mobile applications, has improved land use planning and resource management. About 80% of respondents have access to mobile phones, but only 50% have internet access, suggesting barriers to digital adoption. While ICTs have the potential to enhance rural development, challenges such as digital literacy and infrastructure deficiencies remain a barrier. Strategic investments and collaboration between stakeholders are needed to maximize the impact of ICTs. This research demonstrates that ICT integration in rural planning can foster sustainable development. Although significant challenges exist, recommendations including investment in digital infrastructure and digital literacy training programs are essential to optimize the benefits of ICT for rural communities. Strategic implementation of such recommendations can transform rural communities towards a more sustainable and resilient future.